2019
DOI: 10.1364/josab.36.002757
|View full text |Cite
|
Sign up to set email alerts
|

Orbital angular momentum transfer via spontaneously generated coherence

Abstract: We study the orbital angular momentum (OAM) transfer from a weak Laguerre-Gaussian (LG) field to a weak plane-wave in two closed-loop three-level V -type atomic systems. In the first scheme, the atomic system has two non-degenerate upper levels which the corresponding transition is excited by a microwave plane-wave. It is analytically shown that the microwave field induces an OAM transfer from an LG field to a generated third field. In the second scheme, we consider a three-level V -type atomic system with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…21 ] whereas ⃗ E pr ∝ Ω pr . Under slowly varying envelope approximation (SVEA) and paraxial approximation, the time-independent Maxwell's wave equation for the propagation of probe beam along z direction can be obtained as [25,28,29],…”
Section: Dynamics Of Probe Beam Propagation Through the Atomic Mediummentioning
confidence: 99%
See 2 more Smart Citations
“…21 ] whereas ⃗ E pr ∝ Ω pr . Under slowly varying envelope approximation (SVEA) and paraxial approximation, the time-independent Maxwell's wave equation for the propagation of probe beam along z direction can be obtained as [25,28,29],…”
Section: Dynamics Of Probe Beam Propagation Through the Atomic Mediummentioning
confidence: 99%
“…They have found that due to closed loop structure of the CTL system, the non-vortex (Gaussian) probe beam explicitly depends on the OAM of the vortex control beam. Sabegh et al [25] also investigated the spatially dependent probe responses (absorption and dispersion profiles) and the generation of fourth field (GFF) in a closed-loop fourlevel Ξ-type atomic system. Further, they have shown that the microwave-induced OAM transfer be the crucial factor to generate spatially dependent optical responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various theoretical works have been done to determine the role of the SGC in the bistability and mulistability 35 , 36 , atom-photon entanglement 37 , 38 in different atomic systems. Recently, it has been shown that SGC is capable of transferring the orbital angular momentum from a Laguerre–Gaussian field to a weak plane wave 39 . Moreover, Mahmoudi et.al showed that atoms can be cooled to even below recoil temperature under a cooling mechanism based on SGC-induced electromagnetically induced transparency 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The generation of an OAM-carrying ultraviolet (UV) light through SHG and OAM-entanglement frequency transducer has been experimentally examined by Zhou et al [34,35]. Recent studies deal with the interaction of matter with twisted light and explore the possibility of exchange of optical vortices between different light frequencies [36][37][38][39][40][41][42][43][44][45][46]. Juzelinūas team realized the exchange of OAM modes in four-and five-level quantum systems [43,44].…”
Section: Introductionmentioning
confidence: 99%